New insight into nucleotide changes on irradiated Bactrocera dorsalis (Hendel), a pest of horticultural importance - Yusof, Suhana; Othman, Nurul Wahida; Mohamad Dzomir, Ahmad Zainuri; Mohammed, Muhamad Azmi; Aman Zuki, Ameyra; Yaakop, Salmah (Penerbit Universiti Sains Malaysia, 2024)
Bactrocera dorsalis (Hendel) is a major quarantine pest species infesting most of the tropical fruits. Its infestation had significantly reduced and disrupted the export market trade, thus, very crucial to be controlled during the preharvest and postharvest. One of the most sustainable control methods is by using the radiation technique to reduce the pest population, thus curbing the spread of this pest to new geographical areas. The objective of this study was to measure the nucleotide changes in B. dorsalis (larval, pupal and adult stages) which had been irradiated with 50 to 400 Gray, using Gamma Cell Biobeam GM8000 irradiator with Cesium-137 source at the Malaysian Nuclear Agency, Selangor, Malaysia. Data from the treated samples (with and without morphological changes) were analysed using cytochrome oxidase subunit I (COI). The alignment of 59 sequences resulted in 0.92% variables with only four characters that were parsimony informative, and six sites (30, 60, 234, 282, 483 and 589) which had nucleotide changes, but had not been translated to another protein. Low polymorphism was presented on the sample groups, with only four haplotypes, but with high diversity value (Hd) = 0.5885. The phylogeny trees formed soft polytomy in both trees [neighbour joining (NJ) and maximum parsimony (MP)] presenting a mixture of individuals but did not show any significant difference between treatments. This finding concluded that low mutation had occurred on the treated B. dorsalis and this information is very valuable in getting new insight on the survival of B. dorsalis in the horticulture industry.